1995
DOI: 10.1111/j.1600-0536.1995.tb00808.x
|View full text |Cite
|
Sign up to set email alerts
|

Irritant effects of a detergent in wash and chamber tests

Abstract: Irritant properties of detergents can be tested by using patch and chamber tests and various kinds of use tests. The aim of the present study was to compare the results of use and 12 mm Finn Chamber tests. Study subjects (10 atopic and 11 non-atopic medical students) washed the outer aspect of 1 upper arm with liquid detergent for 1 minute 2 x daily for 1 week. 48-h chamber test with 5 concentrations of the same detergent in water were concurrently applied to upper back skin. Transepidermal water loss (TEWL), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…In the washing test [45], subjects are asked to wash their face with a specific soap or detergent. After washing, individual sensation for tightness, burning, itching and stinging, is evaluated using a point scale previously determined.…”
Section: Washing and Exaggerated Immersion Testsmentioning
confidence: 99%
“…In the washing test [45], subjects are asked to wash their face with a specific soap or detergent. After washing, individual sensation for tightness, burning, itching and stinging, is evaluated using a point scale previously determined.…”
Section: Washing and Exaggerated Immersion Testsmentioning
confidence: 99%
“…Most authors utilized only patch testing; yet, Hannuksela et al (5,8) found significant differences in the results after patch testing and open (non-occluded) application. They documented equal irritancy in atopics and controls in a detergent use test, whereas in a chamber test with 10% aqueous detergent, TEWL increase was significantly higher in atopics than controls.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiologic data (1,2) and several controlled experiments (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)22) suggest they may be more prone to acute irritation than a normal population. For this reason, atopic patients, on the threshold of their choice of occupation, are sometimes advised to avoid industries with an increased risk of irritant contact dermatitis (3).…”
mentioning
confidence: 99%
See 2 more Smart Citations